Single-cell RNA sequencing reveals profibrotic roles of distinct epithelial and mesenchymal lineages in pulmonary fibrosis - Habermann, Arun C.; Gutierrez, Austin J.; Bui, Linh T.; Yahn, Stephanie L.; Winters, Nichelle I.; Calvi, Carla L.; Peter, Lance; Chung, Mei-I; Taylor, Chase J.; Jetter, Christopher; Raju, Latha; Roberson, Jamie; et al. (Science advances, 2020)
Single-cell RNA sequencing provides new insights into pathologic epithelial and mesenchymal remodeling in the human lung. Pulmonary fibrosis (PF) is a form of chronic lung disease characterized by pathologic epithelial remodeling and accumulation of extracellular matrix (ECM). To comprehensively define the cell types, mechanisms, and mediators driving fibrotic remodeling in lungs with PF, we performed single-cell RNA sequencing of single-cell suspensions from 10 nonfibrotic control and 20 PF lungs. Analysis of 114,396 cells identified 31 distinct cell subsets/states. We report that a remarkable shift in epithelial cell phenotypes occurs in the peripheral lung in PF and identify several previously unrecognized epithelial cell phenotypes, including a KRT5 − / KRT17 + pathologic, ECM-producing epithelial cell population that was highly enriched in PF lungs. Multiple fibroblast subtypes were observed to contribute to ECM expansion in a spatially discrete manner. Together, these data provide high-resolution insights into the complexity and plasticity of the distal lung epithelium in human disease and indicate a diversity of epithelial and mesenchymal cells contribute to pathologic lung fibrosis.